Understanding the Montessori approach early years education in practice - Isaacs, Barbara 1949- (London Routledge, 2012)
"Understanding the Montessori Approach is a much needed source of information for those wishing to extend and consolidate their understanding of the Montessori Approach and how it is used in the teaching and learning of young children. It will enable the reader to analyse the essential elements of this Approach to early childhood and and its relationship to quality early years practice.Exploring all areas of the curriculum including the organisation of Montessori schools, the environment, learning and teaching and the outcomes for children this book:focuses on the key principles of the Montessori approach; explores ideas for working with parents and communities around the world;includes a chapter on the benefits and challenges of the Montessori Approach to childrens lives;highlights the key ideas that practitioners should consider when reviewing and reflecting on their own practice;can be used as the basis for continuing professional development and action researchWritten to support the work of all those in the field of early years education and childcare, this is a vital text for students, early years and childcare practitioners, teachers, early years professionals, childrens centre professionals, lecturers, advisory teachers, head teachers and setting managers"--Provided by publisher.
Machine generated contents note: 1.Historical context -- 2.Montessori's views of children's development -- 3.Organisation of Montessori schools -- 4.Learning and teaching -- 5.The favourable environment -- 6.The benefits and challenges of the Montessori approach to children's lives and communities of today.
Includes bibliographical references and index.
Keywords: Montessori method of education